World peace - "Chattopadhyay, Santi Nath (ed.)" (Kolkata, 2005)
This book covers the following topics: Gleanings from the leaders of men; Global vision of peace thinkers; Violence and constructive ways of peace; Contemporary world crises and prospect of global understanding; Sciences and the development of intercultural relation;philosophy,religion and spiritual harmony; aesthetics and creative humanity; value, freedom and peace etc.
Keywords: World peace